A UJI MIKROBIOLOGIS KELAYAKAN MINUMAN ES JERUK PERAS PINGGIR JALAN PONTIANAK TENGGARA - Marizca Okta Syafani; Mahyarudin; Muhammad In’am Ilmiawan (Universitas Widya Gama Mahakam Samarinda, 2022)
Background: Squash orange squash is a natural drink with the ingredients consist of ice and oranges that are sold in many places such as eatery and vendor. Iced orange squash might not be safe for consumption because bad quality oranges, unclean water, unhygienic sellers, and unstandarlized environmental sanitation of the beverage processing. These could cause indigestion with the symptoms of nausea, stomachache, vomitting and diarrhea. The bacteria often used as the indicator that causes contamination in the beverage is Coliform, for example Escherichia coli. Objectives: To find out about the food safety of iced orange squash in Southeast Pontianak. Research Metodes: This research is descriptive with cross-sectional approach. This research uses bacterial quantification method with Most Probable Number (MPN) as the technique and purposive sampling as the sampling method. Results: This research indicates that 16 samples of Squeezed Orange ice exceed the maximum microbial limit that is with the value range of 20 MPN/100 ml - >1100 MPN/ 100 ml contaminated with Coliform (100%) and Escherichia coli (100%). Conclusion: The tested iced orange squash drinks are not safe to consume and unstandardized according to Permenkes 2010, National Standard of Indonesia and World Health Organization.